Salt Water Induced Blepharitis: A Lifestyle-Related Case from a Coast of Java - Pradana, Yuda; Prinasetya, Ki Ajeng W. N. (Universitas Airlangga, 2024)
Introduction: Blepharitis is a disease that is often countered. This condition could occur in all ages, sexes, and ethnic groups. Several factors can be the cause of blepharitis. However, blepharitis cases caused by saltwater have never been reported. Case Presentation: There was a case of a 62-year-old woman who came to the hospital complaining of a foreign body sensation in both eyes. Through examination, it was found that the eyelashes looked dirty with brownish-yellow deposits. Management by doing eyelid hygiene, giving ofloxacin eye drops, NaCl / KCl eye drops, and hygiene education had been done. Conclusions: Blepharitis is a frequently encountered case. However, blepharitis caused by salt water has not been reported. Through this case, it could be learned that the patient's lifestyle and geographical location of the patient's residence must be of particular concern to the clinician.